The effectiveness of incentivized and non-incentivized vessel speed reduction programs: Case study in the Santa Barbara channel. (1st November 2017) - Freedman, Ryan; Herron, Sean; Byrd, Mary; Birney, Kristi; Morten, Jessica; Shafritz, Brian; Caldow, Chris; Hastings, Sean
Highlights: Incentivized approaches effectively slow vessel traffic for conservation benefits. Incentivized slow transits do not affect vessel behavior outside of program areas. Compared to incentive programs, voluntary slow speed programs have low compliance. Managers can implement incentive programs to affect shipping company behavior.